Biogenic Reworking of Tephra Layers in the South China Sea (Core MD972142) and the Celebes Sea (Core MD012388) - Lowemark Ludvig; Chung-Hua Chen; Chih-An Huh; Teh-Quei Lee; Yuen-Ping Ku; Kuo-Yen Wei; Chih-Wei Chen; Tzu-Chien Chiu; Min-Te Chen (Ikatan Ahli Geologi Indonesia, 2004)
Bioturbation in oxic deep-sea settings is mostly considered, if considered at all, to consist of a 2-10 centimeters thick homogenized layer. The mixing of the sediment in this layer results in a smearing of any environmental signals analyzed. A number of mathematical approaches have thereenfore been proposed to estimate the extent of this smearing and smoothing and to deconvolute the records back into the original signal. However, in most cases the mixing of the sediment is heterogenous process consisting of several palimpsest steps of bioturbation. In this study, using X-ray radiographs of two cores from the South China Sea and the Celebes Sea, we show that discrete traces such as Scolicia, Thalassinoides, and Zoophycos account for a significant part of the redistribution of the material in tephra layers. Particles may be transported vertically over tens of cm and concentrated into discrete aggregations. The composition of the traces preserved also can be used to estimate the intensity and potential hazard of deep-reaching bioturbation. Deep-reaching burrows consitute a serious threat to high-resolution stratigraphy. It is therefore recommended that X-ray radiographs should routinely be made before sub-sampling the cores for paleoceanographical and paleoclimatological studies, especially before AMS-14C dating.